Contribución al estudio de la buena fe en el Derecho Privado: a propósito de la renegociación y el incumplimiento de los deberes secundarios de conducta - Vásquez Laguna, Javier (2021)
This essay approaches the study of the principle of good faith, secondary performance obligations and the effects of non-compliance. For this, the study of good faith is approached in its double subjective and objective dimension, as a limit to private autonomy, as well as in its role of interpretation criterion and performance guide. Based on the aforementioned aspects, the effects of non-compliance of secondary duties of conduct are developed and the possibility of activating a termination mechanism for violation of the renegotiation duty is postulated.